Studies on on-line state and parameter estimation through a real-time process simulator - Azevedo, S. Feyo de (1992)
A PC-based simulator of non-linear multiple-input multiple-output dynamic systems was employed for studies concerning the on-line estimation of both 'non-measured' state variables and multiple specific growth rates of a virtual baker´s yeast fed-batch fermentation. The identification algorithms were implemented in an 'Observer Computer' which received, optionally in 'real-time', in 'scaled time' or in 'simulation time', the 'measured' state variables generated by the process simulator in the 'Process Computer'. The state observer showed a robust behaviour under different situations where process parameters, operating variables and measuring characteristics (noise and delays) were changed in the process computer. The simulation package was seen to be an efficient and cheap tool for the simulation of non-linear processes with time varying parameters, providing a realistic environment for tests of identification, estimation and control strategies.